Sphingosine kinase 1 promotes M2 macrophage infiltration and enhances glioma cell migration via the JAK2/STAT3 pathway - Zihan Song; Zijun Zhao; Xuehua Liu; Yiran Song; Siyu Zhu; Ziyang Jia; Yijie Li; Zairan Wang; Boyu Sun; Qianxu Jin; Shiyang Zhang; Zongmao Zhao; et al. (Scientific Reports)
Abstract Sphingosine kinase 1 (SPHK1) is a member of the SPHK family, enzymes essential for the phosphorylation of sphingosine to sphingosine-1-phosphate (S1P). Previous studies have revealed important roles of SPHK1 in inflammatory, anti-apoptotic, immune processes, and cancer. Although the predictive significance and possible roles of SPHK1 in gliomas have recently been examined, the precise molecular mechanisms remain unclear. We comprehensively examined SPHK1 and investigated its correlation with glioma survival time using different datasets. The correlation between SPHK1 and various cancer pathways was analyzed using the Kyoto encyclopedia of genes and genomes (KEGG) analysis. The SPHK1 influence on glioma migration was examined using transwell and wound healing experiments. M2 macrophage infiltration experiments investigated SPHK1’s role in the glioma immune microenvironment. We identified SPHK1 downstream pathways and further elucidated their regulatory relationship. Survival analysis illustrated that patients with high-SPHK1 expression, particularly glioblastoma and IDH-wildtype, tended to have a shorter survival time. The Cox regression model (COX) results demonstrated that SPHK1 was an independent prognostic factor affecting the survival of patients with glioma. Functional experiments illustrated that SPHK1 suppression led to a reduction in the migration capacity of glioma cells. Enrichment analysis and Western blotting revealed that SPHK1 functions as a JAK2/STAT3 pathway controller. The SPHK1 overexpression-induced migration was suppressed by the JAK2/STAT3 pathway suppressor (AG490). We found that SPHK1 promotes M2 macrophage infiltration. Further study indicated that SPHK1 could serve as a prognostic indicator of glioma and promote cell migration, providing new insights for glioma therapy.